Chronic Illness, Spirituality, and Healing
XIII, 308 p. 2 illus.
Keywords: Fusing the disciplines of health care, spiritual care, and social services, this book examines the relationship between chronic illness and spirituality. Contributors include professionals working in traditional, holistic and integrative clinical settings, as well as religious studies scholars and spiritual practitioners.